PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POWERPOINT UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS X SMA NEGERI 1 HILIMEGAI - Laia, Murniba (Universitas Nias Raya, 2024)
This research was motivated by the unavailability of powerpoint learning media, which resulted in students being less motivates to study the subject of the human.. This research aims to determine the effect of using PowerPoint learning media to increase students' interest in learning in class X Biology at SMA Negeri 1 Hilimegai. The type of research is quantitative, descriptive in nature. The research population was class X students of SMA Negeri 1 Hilimegai while the research sample was class This research data was analyzed using normality tests and hypothesis testing using the SPSS (Statistical Product and Service Solution) application. The results of this research are that the sig.(2-tailed) value is 0.015 < 0.05, it is known that t count is 2.597 < t table 2.65183, it is known that the value of sig. > t table 2.25183 for the experimental class using PowerPoint learning media, it can be concluded that the data is normally distributed so that students have an interest in participating in learning activities through PowerPoint learning media. Suggestion: for teachers, it is best to use PowerPoint learning media with different variations, for future researchers it is best to carry out this research with a wider scope.